The influence of language learner’s Buddhist background on non-native written language processing - Darzhinova, Liubov V. (The New Research of Tuva, 2021)
In today’s digitalized world, discovering approaches to enhance written language processing is crucial for successful non-native language acquisition. Whereas psycholinguistic literature suggests that background knowledge generally facilitates written language processing, hardly anything is known about whether religious affiliation as a part of language learner’s background affects non-native written language processing. Consequently, the current paper addresses the gap by conducting a small-scale web-based self-paced reading study. It explores whether English language learners with Buddhist background process the Buddhist-related and religiously neutral texts similarly to those with the same proficiency level but with no religious affiliation. Thus, the experiment involved 20 Buddhist and non-religious learners of English from Russia’s regions of Kalmykia, Tuva, and Buryatia. The results of the experiment suggest that the Buddhist background of English language learners contributes to faster processing and better recall of Buddhist-related texts in the target language. The paper argues for the need to supply written materials related to religion in a target language with notes and glossaries in order to hasten processing and improve recall in non-religious language learners.